2021
DOI: 10.21873/anticanres.14800
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dense Neoadjuvant Chemotherapy With Paclitaxel and Carboplatin in Cervical Cancer: Efficacy on Pathological Response

Abstract: Background/Aim: The role of neoadjuvant chemotherapy (NACT) is under investigation in locally advanced cervical cancer (LACC). Patients and Methods: A total of 49 patients with FIGO stage IB1-IIB cervical cancer who underwent two different regimens of weekly dose-dense NACT were included. The objective was to evaluate clinical/pathological response and toxicity profile. Results: A clinical complete response and partial response were obtained in 43 patients with a clinical overall response rate of 88%. Among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Consequently, this resulted in a noticeable decrease in SCC-Ag, CEA, and CA125 levels in patients undergoing combined treatment. Additionally, while surgery focuses on the mechanical removal of the tumor, neoadjuvant chemotherapy effectively inhibits and destroys cancer cells at a molecular level [20].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, this resulted in a noticeable decrease in SCC-Ag, CEA, and CA125 levels in patients undergoing combined treatment. Additionally, while surgery focuses on the mechanical removal of the tumor, neoadjuvant chemotherapy effectively inhibits and destroys cancer cells at a molecular level [20].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies consistently reported low 5-year survival rates among cervical cancer patients, regardless of whether surgery or radiation therapy was utilized, suggesting a substantial need for improved efficacy in both surgical and radiation treatments [9,10]. Previously, chemotherapy was seldom prescribed in the clinical treatment of cervical cancer patients due to the prevailing belief that cervical cancer lesions exhibited limited sensitivity to chemotherapeutic agents [11,12]. However, with the introduction of neoadjuvant chemotherapy in cervical cancer treatment, researchers across multiple locations have begun to further assess this treatment approach by conducting in-depth analyses of specific neoadjuvant chemotherapy regimens used for cervical cancer treatment, including the optimal types and dosages of chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ovarian carcinoma, NAC has been utilized for the management of other malignancies, including carcinomas of the breast, lung, stomach, and rectum (23)(24)(25)(26)(27); its effects on the histomorphology of these tumors have been well documented (12,13,20,21). Chemotherapy-induced morphological changes in the ovary have been described in several studies.…”
Section: Discussionmentioning
confidence: 99%